TIR1-produced cAMP as a second messenger in transcriptional auxin signalling - Huihuang Chen; Linlin Qi; Minxia Zou; Mengting Lu; Mateusz Kwiatkowski; Yuanrong Pei; Krzysztof Jaworski; Jiří Friml (Nature, 2025)
Abstract The phytohormone auxin (Aux) is a principal endogenous developmental signal in plants. It mediates transcriptional reprogramming by a well-established canonical signalling mechanism. TIR1/AFB auxin receptors are F-box subunits of an ubiquitin ligase complex; after auxin perception, they associate with Aux/IAA transcriptional repressors and ubiquitinate them for degradation, thus enabling the activation of auxin response factor (ARF) transcription factors1–3. Here we revise this paradigm by showing that without TIR1 adenylate cyclase (AC) activity4, auxin-induced degradation of Aux/IAAs is not sufficient to mediate the transcriptional auxin response. Abolishing the TIR1 AC activity does not affect auxin-induced degradation of Aux/IAAs but renders TIR1 non-functional in mediating transcriptional reprogramming and auxin-regulated development, including shoot, root, root hair growth and lateral root formation. Transgenic plants show that local cAMP production in the vicinity of the Aux/IAA–ARF complex by unrelated AC enzymes bypasses the need for auxin perception and is sufficient to induce ARF-mediated transcription. These discoveries revise the canonical model of auxin signalling and establish TIR1/AFB-produced cAMP as a second messenger essential for transcriptional reprograming.